Blood-based non-Newtonian ternary nanofluid flow in converging/diverging channels embedded in a non-Darcy porous medium with slip and jump effects - Gunay, Tunahan; Erdem, Duygu; Sahin, Ahmet Ziyaettin; Öztop, Hakan Fehmi (Emerald Group Publishing Ltd, 2026)
PurposeNanoparticles are well-suited for targeted drug delivery and thermal cancer therapy due to their high surface area in proportion to their volume. Blood acts like a Newtonian fluid at high shear rates, whereas it exhibits non-Newtonian behavior at low shear rates. In addition, ternary hybrid nanofluids (THNFs) can have enhanced thermophysical properties over single and two-particle nanofluids because of their combined effects. Based on this knowledge, the purpose of this study is to examine the flow of blood-based second-grade THNF in converging/diverging channels, considering slip-velocity and temperature jump effects.Design/methodology/approachGoverning nonlinear partial differential equations for continuity, momentum and energy were transformed to ordinary differential equations (ODEs) using similarity variables, and these ODEs are solved numerically with MATLAB's bvp4c function. The accuracy of the numerical solution is validated by comparing results with established literature, showing close agreement.FindingsThe influence of various parameters on velocity and temperature profiles, as well as on engineering parameters, is investigated. The Darcy and Forchheimer parameters, which are in the range of 0-2, demonstrate an inverse relationship in converging and diverging channels. Higher Darcy and inertial parameters improve skin friction and heat transfer in the diverging channel but decrease them in the converging channel. When the Deborah number ranges from 0 to 0.3, the non-Newtonian fluid's elastic properties generate a 3% velocity field difference. Nanoparticle shape factor and volume fraction play vital roles in optimizing heat transfer.Research limitations/implicationsThe results of this study could be valuable in engineering applications that investigate the effect of nanofluids in blood vessels.Originality/valueThe key innovation of this study includes the investigation of blood-based THNF flow in converging/diverging channels embedded in a non-Darcy porous medium across different vessel sizes by using a non-Newtonian model.
Keywords: Ternary hybrid nanofluid; Blood flow; Non-Newtonian fluid; Non-Darcy porous medium; Thermal radiation; Slip effects